'Although we're isolated, we're not really isolated': The value of information and communication technology for older people in rural Australia. (22nd June 2017) - Berg, Turi; Winterton, Rachel; Petersen, Maree; Warburton, Jeni
Abstract : Objective: Drawing from a larger study that identified the supports and services that facilitate wellness among older people from rural communities, this study examined the specific contribution made by information and communication technology (ICT). Methods: Qualitative interviews were undertaken with 60 older adults from six Australian rural areas. A preliminary thematic analysis was conducted, followed by a higher‐order inductive analysis. Results: Information and communication technology use was discussed in terms of individual enrichment, and in terms of enabling connections between the individual and their social networks, community and wider service environments. Conclusion: Information and communication technologies may facilitate wellness for rural older people by compensating for geographical and social isolation. In the changing world of health and aged care service delivery, ICTs will be more important than ever for rural older people in building their capacity to access the services, socialisation and support that they need, regardless of location.